ISU PASCA IMPLEMENTASI PSAK 73 DARI SUDUT PANDANG EKSTERNAL AUDIT - Trisha Thalia (Owner : Riset dan Jurnal Akuntansi, 2023)
This study aims to identify post-implementation issues of PSAK 73 in companies in Indonesia from 2020, through the perspective of a public accounting firm, KAP XYZ, and provide solutions to issues that still arise until 2022, which is the third year of PSAK 73 implementation. The implementation of PSAK 73, which began in 2020, has forced many companies in Indonesia to adapt their lease contracts and calculations related to their leases. The significant change from PSAK 30 to PSAK 73 caused a lot of confusion and errors in its application to companies in Indonesia. This research was conducted at one of the top ten public accounting firms in Indonesia, where most clients of the public accounting firm have an obligation to apply PSAK 73. The research instruments used in this study include in-depth interviews. The data analysis used in this research is descriptive analysis, with an inductive approach. The results of this study shows that there are many issues that occurred in the first year of implementation of PSAK 73 on KAP XYZ clients, where most clients did not correctly implement PSAK 73 in the first year. In addition, many clients make contract amendments to avoid the application of PSAK 73. Auditors from KAP XYZ were consulting and guiding clients in implementing PSAK 73 on their financial statements since 2020 until present time, to minimize similar miscalculations to happen in the following years.